Identifikasi Perencanaan, Implementasi dan Evaluasi Program Corporate Social Responsibility Perusahaan Karet di Kabupaten Tulang Bawang Barat, Lampung - Sumaryo Gitosaputro; Sahrul Ari Irawan (Universitas Sebelas Maret, 2024)
Corporate social responsibility (CSR) is one of the mandatory programs implemented by companies that contributes to the progress of the nation. Private companies, state-owned companies, and Regional-Owned Enterprises (BUMD), especially private companies, are not entirely optimal in implementing CSR. This study aims to determine the extent to which CSR planning, implementation, and evaluation at PT. Huma Indah Mekar are given to the community around the company's area. This study is a field study accompanied by an internship. The research is a qualitative descriptive type using interviews and observations as research instruments. The research was conducted at PT. Huma Indah Mekar by making human resource development (HRD) and HRD Staff as informants. The results of this study show that the CSR program in the company has been well planned, from building renovation, education scholarships, blood donation, and mass circumcision. The targets, objectives, and implementation forms have been prepared and planned well by the company's CSR team. The implementation of this CSR program includes the place, actors, objects, and feelings of the community around the recipients of the CSR program. The evaluation of the program that has been implemented provides an illustration of the need for improvement and re-planning of future CSR programs.